2009
DOI: 10.1159/000228929
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders in Alcohol-Dependent Individuals: Relationship with Alcohol Dependence Severity

Abstract: The rate of axis II disorders in alcohol-dependent individuals is suggested to be high. The aim of this investigation is to assess the rate of DSM-IV axis II diagnoses in alcohol-dependent inpatients and their correlation with clinical characteristics of alcohol dependence (AD). 1,079 inpatients with DSM-IV AD from three inpatient addiction treatment centers (‘qualified detoxification’, open psychiatric university hospital wards) were included. Characteristics of AD were obtained using standardized structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 60 publications
5
26
0
4
Order By: Relevance
“…They are consistent with numerous published reports indicating that comorbid mood disorders are more prominent among women than men presenting for SUD treatment (see review by Pettinati and Plebani, 2009). To our knowledge, stronger comorbid associations of any drug dependence with narcissistic PD among men have not previously been reported except in the NESARC sample , and this sex difference has not been reported at all for cannabis dependence, although Preuss et al (2009) reported a signifi cantly higher prevalence of narcissistic PD among male than among female patients with alcohol dependence.…”
Section: Discussionmentioning
confidence: 53%
“…They are consistent with numerous published reports indicating that comorbid mood disorders are more prominent among women than men presenting for SUD treatment (see review by Pettinati and Plebani, 2009). To our knowledge, stronger comorbid associations of any drug dependence with narcissistic PD among men have not previously been reported except in the NESARC sample , and this sex difference has not been reported at all for cannabis dependence, although Preuss et al (2009) reported a signifi cantly higher prevalence of narcissistic PD among male than among female patients with alcohol dependence.…”
Section: Discussionmentioning
confidence: 53%
“…However, so far it is not clear if in humans the same personality characteristics reported to be associated with alcohol dependence are also good predictors of relapse. As reported in several studies, alcohol dependence is associated with antisocial behaviour [3,4] as well as with anxiety and mood disturbances [5,6]. This is reflected by high scores on personality scales measuring aggression, impulsivity and sensation seeking, as well as traits related to neuroticism which is marked by stress sensitivity, anxiety and depression [4,5,6,7,8,9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 93%
“…Neurobiological and environmental conditions of relapse have been widely studied in animals and humans [2]. Psychiatric disturbances as well as personality traits have been investigated as predictors or indicators of alcohol dependence [3,4,5,6]. However, so far it is not clear if in humans the same personality characteristics reported to be associated with alcohol dependence are also good predictors of relapse.…”
Section: Introductionmentioning
confidence: 99%
“…En muestras de drogodependientes, Preuss et al (2009) encontraron que el 60% de una muestra de alcohólicos presentaba al menos un TP, mientras que Grant et al (2004) encontraron que el 29% de los sujetos con trastorno por uso de alcohol y el 48% de aquellos con trastorno por uso de sustancias presentaban al menos un TP. En consumidores de opiáceos, Frei y Rehm (2002) encontraron que el 42% presentaban TP, mientras que Grella et al (2009) obtuvieron una prevalencia del 50%.…”
unclassified